Legal Study of The Mary Jane Fiesta Veloso Case from Human Rights and International Agreement Perspective - Benedictus See; Albertus D Soge (Universitas Proklamasi 45, 2025)
The purpose of this study is to analyze and understand whether the Mutual Legal Assistance in Criminal Matters (MLA) which is the legal basis for the return of Mary Jane, a death row convict, to her home country, the Philippines, is in accordance with international legal norms and how the provisions of the laws and regulations in force in Indonesia are in this case. This study is a normative legal study that is descriptive and analytical in nature, using the approach of related laws and regulations. Data were obtained through document studies and analyzed using qualitative normative methods. The results of the study indicate that the return of Mary Jane Fiesta Velosa, a death row convict, to the Philippines is based on an Agreement between the Government of Indonesia and the Government of the Philippines in the form of MLA and is based on an agreement between the Government of Indonesia and the Government of the Philippines and the existence of a policy from the President of the Republic of Indonesia to make one decision (Discretion).